What's Up with U.S. Wage Growth and Job Mobility? - Danninger, Stephan (IMF Working Papers; Working Paper, 2016)
Since the global financial crisis, US wage growth has been sluggish. Drawing on individual earnings data from the 2000-15 Current Population Survey, I find that the drawn-out cyclical labor market repair-likely owing to low entry wages of new workers-slowed down real wage growth. There are, however, also signs of structural changes in the labor market affecting wages: for full-time, full-employed workers, the Wage-Phillips curve-the empirical relationship between wage growth and the unemployment rate-has become horizontal after 2008. Similarly, job-turnover rates have continued to decline. Job-to-job transitions-associated with higher wage growth-have slowed across all skill and age groups and beyond what local labor market conditions would imply. This raises concerns about the allocative ability of the labor market to adjust to changing economic conditions.